2010
DOI: 10.1017/s0954579410000283
|View full text |Cite
|
Sign up to set email alerts
|

Developmental cascades of peer relations and symptoms of externalizing and internalizing problems from kindergarten to fourth-grade elementary school

Abstract: A developmental cascade model linking symptoms of externalizing and internalizing psychopathology through three indices of peer relational difficulty (peer rejection, peer victimization, friendedness) was tested in a general population sample of 653 children followed annually from kindergarten to fourth grade. Rejection and victimization linked kindergarten externalizing problems with fourth-grade internalizing problems. Transactional links between rejection and victimization were found. In addition, peer reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
176
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 80 publications
16
176
1
6
Order By: Relevance
“…Unfortunately, not all children have warm relationships with teachers, and problems in this relationship are linked with child maladjustment (Bergin & Bergin, 2009;Thapa, Cohen, Guffey, & Higgins-D'Alessandro, 2013). There is an abundance of evidence showing that adverse social experiences with peers and teachers during the elementary school period are linked to serious negative outcomes, including symptoms of externalizing and internalizing problems, suicidal thoughts and acts with hospitalization, academic underachievement, physical illness and poor self-perceptions (Cillessen & Lansu, 2015;Deater-Deckard, 2001;Hamre & Pianta, 2005;Klomek, Marrocco, Kleinman, Shonfeld, & Gould, 2007, Klomek et al, 2009McDougall & Vaillancourt, 2015;Parker et al, 2006;van Lier & Koot, 2010;Wang, Selman, Dishion, & Stormshak, 2010). Despite the accumulating evidence of the role of adverse social experiences on child maladjustment outcomes, knowledge about the impact of such school social experiences on children's executive functions is limited, particularly with respect to childhood.…”
mentioning
confidence: 99%
“…Unfortunately, not all children have warm relationships with teachers, and problems in this relationship are linked with child maladjustment (Bergin & Bergin, 2009;Thapa, Cohen, Guffey, & Higgins-D'Alessandro, 2013). There is an abundance of evidence showing that adverse social experiences with peers and teachers during the elementary school period are linked to serious negative outcomes, including symptoms of externalizing and internalizing problems, suicidal thoughts and acts with hospitalization, academic underachievement, physical illness and poor self-perceptions (Cillessen & Lansu, 2015;Deater-Deckard, 2001;Hamre & Pianta, 2005;Klomek, Marrocco, Kleinman, Shonfeld, & Gould, 2007, Klomek et al, 2009McDougall & Vaillancourt, 2015;Parker et al, 2006;van Lier & Koot, 2010;Wang, Selman, Dishion, & Stormshak, 2010). Despite the accumulating evidence of the role of adverse social experiences on child maladjustment outcomes, knowledge about the impact of such school social experiences on children's executive functions is limited, particularly with respect to childhood.…”
mentioning
confidence: 99%
“…It has been suggested that CSAP show higher rates of behavioral problems at a younger age than their peers from community samples (Clark et al, 2004;Molina et al, 2010). These problems could contribute to the development of peer relationship difficulties at a later age, as described by van Lier and Koot (2010), who confirmed similar cascading effects in a community sample of school-aged children. The peer relationship problems, rooted in externalizing problem behavior, were, over time, related to the continuation of externalizing and the onset of internalizing problems.…”
Section: Discussionmentioning
confidence: 84%
“…A questão que se coloca neste ponto é se tais ganhos persistiriam além dos seis meses do seguimento. A evidência de processos de retroalimentação, característicos do curso do desenvolvimento do escolar (Burt & Roisman, 2010;Van Lier & Koot, 2010), dá margem a uma visão otimista, no sentido de que as melhoras obtidas possam afetar positivamente a trajetória das crianças. No entanto, a resposta deve ser buscada por meio de estudos de seguimento de longo prazo.…”
Section: Discussionunclassified
“…Estudos recentes têm demonstrado que a predição não segue um modelo causal, mas antes um modelo de influências transacionais, definidas como relações longitudinais intrapessoais recíprocas entre domínios do funcionamento adaptativo (Bornstein et al, 2010). Trajetórias de desenvolvimento com influências entre domínios foram identificadas para habilidades sociais e desempenho acadêmico (Chen et al, 2010), habilidades sociais e problemas de comportamento (Burt & Roisman, 2010;Van Lier & Koot, 2010), desempenho e problemas de comportamento (Moilanen, Shaw, & Maxwell, 2010).…”
unclassified